2017
DOI: 10.1371/journal.pone.0188731
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities and sexual dimorphism in neurotoxic effects of ambient fine particles on youth IQ: A longitudinal analysis

Abstract: Mounting evidence indicates that early-life exposure to particulate air pollutants pose threats to children’s cognitive development, but studies about the neurotoxic effects associated with exposures during adolescence remain unclear. We examined whether exposure to ambient fine particles (PM2.5) at residential locations affects intelligence quotient (IQ) during pre-/early- adolescence (ages 9–11) and emerging adulthood (ages 18–20) in a demographically-diverse population (N = 1,360) residing in Southern Calif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
(56 reference statements)
1
26
0
1
Order By: Relevance
“…In their study, the authors measured IQ scores with the Wechsler Abbreviated Scale of Intelligence 28. The potential effect modification by sex or social class is a newer finding, but Chen points out that the Chinese study is a compelling corroboration of research that Lilian Calderón-Garcidueñas conducted in a highly polluted environment more than 15 years ago.…”
Section: Long-term Effects Of Air Pollutants On the Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, the authors measured IQ scores with the Wechsler Abbreviated Scale of Intelligence 28. The potential effect modification by sex or social class is a newer finding, but Chen points out that the Chinese study is a compelling corroboration of research that Lilian Calderón-Garcidueñas conducted in a highly polluted environment more than 15 years ago.…”
Section: Long-term Effects Of Air Pollutants On the Brainmentioning
confidence: 99%
“…Other studies have associated prolonged exposure to air pollutants in utero or during childhood with reduced academic performance,26 , 27 , 28 a greater risk of autism spectrum disorder,29 , 30 and lower adult earnings 31. For older adults, most studies of long-term exposure have found associations with cognitive decline and neurodegenerative diseases 2 , 32…”
Section: Long-term Effects Of Air Pollutants On the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, two studies examined sex differences in the effect, with one suggesting larger effects in girls (34) and the other reporting no difference between the sexes (37). Given the sex differences seen in the associations between air pollution exposure and cognition, with some studies reporting greater impairments in males compared to females (21, 22, 24, 64, 65), future studies should examine sex as a potential modifier and report summary statistics by sex. Similarly, outdoor air pollution exposure is associated with various adverse health effects in children (66), such as pre-term birth (67, 68), increased BMI (69), increased asthma risk (70), delayed lung function growth (70, 71), and vitamin-D deficiency (72, 73).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the brain's structure and function continues to mature well into the third decade of life (214), the neurotoxic effects of outdoor air pollution may be present throughout the entire dynamic neurodevelopmental process, as a result of exposure from childhood, through adolescence, and into young adulthood (1517). Extant data on neurodevelopmental effects of air pollution suggest that both prenatal and postnatal exposure is associated with deficits in intelligence quotient (IQ) (1822), as well as a broad range of cognitive domains (21, 23, 24), subclinical mental health problems (25, 26) as well as risk for Autism Spectrum Disorders (2729). Together, these findings suggest outdoor air pollution exposure may impact cognitive development and emotional behaviors, yet questions remain regarding the mechanisms influencing the structural and functional brain alterations that may underlie these associations observed in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%